Case Report: Novel GLA mutation in a Chinese female with renal-predominant Fabry disease and cardiac hypertrophy - Li, Lanxin; Chang, Tianyu; Li, Xichen; Hao, Yinglu; Deng, Min; Li, Yanping (Frontiers in Genetics, 2026)
BackgroundFabry disease (FD) is a rare X-linked lysosomal storage disorder caused by GLA gene mutations, leading to deficient α-galactosidase A (α-Gal A) activity and progressive accumulation of globotriaosylceramide (Gb3) and globotriaosylsphingosine (lyso-Gb3) in multiple tissues. Diagnosis remains challenging in late-onset renal-predominant phenotypes.Case descriptionA 72-year-old Chinese female presented with end-stage renal disease (ESRD) and hypertrophic cardiomyopathy, prompting a clinical suspicion of FD. The diagnosis was confirmed by the identification of a novel GLA missense variant, c.522T>G (p.Cys174Trp), which was classified as likely pathogenic. All tested family members who carried this variant exhibited the characteristic biochemical phenotype of reduced α-Gal A activity and elevated lyso-Gb3 levels.ConclusionThis report describes the first documented case of the GLA c.522T>G (p.Cys174Trp) variant, expanding the mutational spectrum of FD in East Asians. The coexistence of ESRD and cardiac hypertrophy should prompt clinicians to consider GLA screening, particularly in females with atypical presentations.